2023
DOI: 10.1177/14771535231203564
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of questionnaire items for discomfort glare studies in daylit spaces

G Quek,
S Jain,
C Karmann
et al.

Abstract: When studying discomfort glare, researchers tend to rely on a single questionnaire item to obtain user evaluations. It is unclear whether the choice of questionnaire item affects the distribution of user responses and leads to inconsistencies between studies. This study aims to investigate if different glare questionnaire items yield similar distributions of user discomfort in daylit environments. We conducted a comparative study of selected questionnaire items from previous glare experiments, testing them in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The gaze direction and position of an occupant are also important for visual discomfort from daylight: Viula et al 7 pointed out that the Daylight Glare Probability metric showed lower predictive performance for occupants at the inner parts of a classroom and proposed modifications to improve discomfort glare predictions in classrooms. Quek et al 8 compared the validity and consistency of existing questionnaires to assess discomfort glare in daylit indoor spaces. Designs with binary, ordinal, and categorical ratings were found to reach similar glare ratings, although thresholds for low level of discomfort did not always coincide.…”
mentioning
confidence: 99%
“…The gaze direction and position of an occupant are also important for visual discomfort from daylight: Viula et al 7 pointed out that the Daylight Glare Probability metric showed lower predictive performance for occupants at the inner parts of a classroom and proposed modifications to improve discomfort glare predictions in classrooms. Quek et al 8 compared the validity and consistency of existing questionnaires to assess discomfort glare in daylit indoor spaces. Designs with binary, ordinal, and categorical ratings were found to reach similar glare ratings, although thresholds for low level of discomfort did not always coincide.…”
mentioning
confidence: 99%